Greater efforts for development of knowledge economy in Vietnam under optics of economic policies - Nguyet Hong, Vu Xuan; Thu Hoai, Dang Thi (Journal SCIENCE AND TECHNOLOGY POLICIES AND MANAGEMENT, 2017)
Development of knowledge economy in actual stage of Vietnam is to enhance the roles and contributions of knowledge and science & technology (S&T) in economy of the country. The promotion of knowledge economy in Vietnam would give contributions to the shift of economic structure which “by 2020 will basically to provide the model of economic growth based on deeply developed sectors, ensure growth of quality, enhance effectiveness and competitiveness of the country”. This paper uses the analysis framework of economic development policies applied by World Bank to demonstrate that the economic policies keep the equally important roles as S&T policies and other policies do for promotion of knowledge economy. Actual economic policies in Vietnam cause a lot of barriers which slow down, and even neutralize positive impacts from S&T policies. This can be seen as deeply rooted causes which do not turn yet S&T to driving forces for development as expected, despite numerous and long-lasting attentions and priorities provided by the Party and the State. In order to recover these negative aspects in the future time, the economic policies should be focused on the establishment of business environment of healthy and equal competition. They need also to enforce enterprises to apply S&T and knowledge based solutions to enhance their market competitiveness.